Paleozoic plays of NW Europe - Monaghan, A. A.; Underhill, J. R.; Hewett, A. J.; Marshall, J. E. A. (The Geological Society, 2019)
Despite successful production from Carboniferous and Permian reservoirs in the southern North Sea and onshore Netherlands and Germany, Paleozoic hydrocarbon plays across parts of NW Europe remain relatively under-explored both onshore and offshore. This volume brings together new and previously unpublished knowledge about the Paleozoic plays of NW Europe to describe significant additional exploration opportunities outside and below existing plays. The volume contains papers on Paleozoic plays in the North Sea, Irish Sea, onshore UK, France and Switzerland. They highlight how improvements in seismic data quality and the availability of previously unpublished well datasets form the basis for improved understanding of local to regional interpretations that move forward from generalized basin development models. The improved structural trap and source rock basin definition feeds to better constrained, locally variable burial, uplift, maturation and migration models. Particularly notable are the significant mapped extents and thickness of Paleozoic source, reservoir and seal rocks in areas previously dismissed as regional highs and platforms.
Keywords: Petroleum -- Geology -- Europe, Northern.; Petroleum -- Prospecting -- Europe, Northern.; Sedimentary basins -- Europe, Northern.; Geology, Stratigraphic -- Paleozoic.; elektronické knihy; electronic books